2014
DOI: 10.1007/s40279-014-0199-1
|View full text |Cite|
|
Sign up to set email alerts
|

Applied Physiology of Female Soccer: An Update

Abstract: The popularity and professionalism of female soccer has increased markedly in recent years, with elite players now employed on either a professional or semi-professional basis. The previous review of the physiological demands of female soccer was undertaken two decades ago when the sport was in its relative infancy. Increased research coupled with greater training and competition demands warrants an updated review to consider the effect on physical performance and injury patterns.The physical demands of match-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
188
4
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(262 citation statements)
references
References 117 publications
12
188
4
19
Order By: Relevance
“…Participation in women football has increased rapidly (Datson et al, 2014;Fahmy, 2011) and similar to men football, success is often determined by tactical and technical qualities. Nevertheless, physical attributes such as high-intensity running performance, repeated-sprint ability and speed are important determinants of successful performance (Gabbett & Mulvey, 2008;Gabbett, Wiig, & Spencer, 2013;Mohr, Krustrup, Andersson, Kirkendal, & Bangsbo, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in women football has increased rapidly (Datson et al, 2014;Fahmy, 2011) and similar to men football, success is often determined by tactical and technical qualities. Nevertheless, physical attributes such as high-intensity running performance, repeated-sprint ability and speed are important determinants of successful performance (Gabbett & Mulvey, 2008;Gabbett, Wiig, & Spencer, 2013;Mohr, Krustrup, Andersson, Kirkendal, & Bangsbo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Match high-intensity running performance is closely related to performance on the yo-yo level 1 recovery (YYIR) (Krustrup, Mohr, Ellingsgaard, & Bangsbo, 2005) while maximal-intensity actions, such as sprinting, occur in close proximity to key moments in football competition (Faude, Koch, & Myer, 2012). Thus, high-intensity running capability and sprint performance are of great importance in football (Datson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Women's soccer is growing rapidly in popularity with increasing participation rates worldwide (10,13). There are now opportunities for players to become professional in both the United States of America and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing numbers of young females involved in soccer training and competition (Datson et al, 2014) In the adolescent population, we have previously demonstrated no difference in deoxyhaemoglobin (HHb) kinetics between trained soccer players and recreationally active controls during the transition to moderate intensity exercise (Marwood et al 2010). kinetics is due to an equal contribution of adaptations in oxygen delivery and utilization, whereas the latter indicates that adaptations in oxygen utilization are relatively more important.…”
mentioning
confidence: 99%